Chemoreactomic analysis of thiamine disulfide, thiamine hydrochloride, and benfotiamine molecules - O. A. Gromova; I. Yu. Torshin; L. V. Stakhovskaya; L. E. Fedotova (Неврология, нейропсихиатрия, психосоматика, 2017)
Objective: to analyze the interactions that could indicate the potential pharmacological properties of the molecules of thiamin, thiamine disulfide, and others.Material and methods. The investigators simulated the properties of thiamine disulfide (bistiamin) versus those of the reference molecules of thiamin hydrochloride and benfotiamine. The study was performed using chemoreactomic simulation that is the newest area in post-genome pharmacology.Results and discussion. Chemoreactomic analysis has shown that thiamine disulfide can inhibit the molecular receptors involved in blood pressure regulation: adrenoceptors, vasopressin receptor, and angiotensin receptor. Thiamine disulfide can inhibit the reuptake of serotonin, increase its levels, inhibit benzodiazepine receptor and dopamine reuptake, and enhance neuronal acetylcholine release to a large extent than benfotiamine. These molecular effects are consistent with the sedative and anticonvulsant action profile of thiamine disulfide. Simulation has indicated that thiamine disulfide has neuroprotective, anti-inflammatory, normolipidemic, and antitumor activities.Conclusion. The simulation results are confirmed by the available clinical and experimental findings and indicate the virtually unstudied molecular mechanisms of action of thiamine disulfide, benfotiamine, and thiamin hydrochloride.